Knowledge management and firm innovative performance with the moderating role of transformational leadership - Irene, Wei Kiong Ting; Sui, Hai Juan; Qian, Long Kweh; Nawanir, Gusman (Emerald Publishing Limited, 2021)
Purpose This study aims to examine the effect of knowledge management on firm innovative performance and the moderating effect of transformational leadership in the relationship between knowledge management and firm innovative performance.